The snow queen [large type] : a novel - Cunningham, Michael, 1952- (Center Point Large Print, 2015)
"The Meeks brothers travel down different paths in search for transcendence. Barrett, haunted by a vision of light, turns unexpectedly to religion. Tyler grows increasingly convinced that only drugs can release his creative powers"--